2020
DOI: 10.1103/physrevmaterials.4.055001
|View full text |Cite
|
Sign up to set email alerts
|

Phase stabilities ofMgCO3andMgCO3-II studied by Raman spectroscopy, x-ray diffraction, and density functional theory calculations

Abstract: Carbonates are the major hosts of carbon on Earth's surface and their fate during subduction needs to be known to understand the deep carbon cycle. Magnesite (MgCO 3 ) is thought to be an important phase participating in deep Earth processes, but its phase stability is still a matter of debate for the conditions prevalent in the lowest part of the mantle and at the core mantle boundary. Here, we have studied the phase relations and stabilities of MgCO 3 at these P, T conditions, using Raman spectroscopy at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 67 publications
2
44
0
Order By: Relevance
“…The pressure/temperature conditions of the reversal reaction as constrained by these experiments are similar to those of polymorphic phase transitions associated with sp -sp 3 bonding changes in both MgCO 3 and CaCO 3 , which suggests these transitions are related to the stabilization of a CaCO 3 + MgSiO 3 assemblage. The transition from sp 2 -to sp 3 bonds in MgCO 3 has been identified at~80 GPa with the stabilization of the C2/m structure 32,33,36 , and the resulting densification of MgCO 3 supports the forward reaction to MgCO 3 + CaSiO 3 . The transition in CaCO 3 from sp 2 -to sp 3 bonds in the P2 1 /c-h structure was experimentally observed at~105 GPa and 2000 K 37 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The pressure/temperature conditions of the reversal reaction as constrained by these experiments are similar to those of polymorphic phase transitions associated with sp -sp 3 bonding changes in both MgCO 3 and CaCO 3 , which suggests these transitions are related to the stabilization of a CaCO 3 + MgSiO 3 assemblage. The transition from sp 2 -to sp 3 bonds in MgCO 3 has been identified at~80 GPa with the stabilization of the C2/m structure 32,33,36 , and the resulting densification of MgCO 3 supports the forward reaction to MgCO 3 + CaSiO 3 . The transition in CaCO 3 from sp 2 -to sp 3 bonds in the P2 1 /c-h structure was experimentally observed at~105 GPa and 2000 K 37 .…”
Section: Discussionmentioning
confidence: 87%
“…Theoretical studies further predict that MgCO 3 + CaSiO 3 are enthalpically favored over CaCO 3 + MgSiO 3 throughout the lower mantle pressure and temperature regime [26][27][28][29][30] . However, although many studies have addressed the stability of individual carbonates up to higher pressures [31][32][33] , no experiments examined the carbonate-silicate cation exchange reaction up to core-mantle boundary conditions.…”
mentioning
confidence: 99%
“…Within the last two decades, several studies showed that all major carbonates, such as CaCO 3 (Bayarjargal et al, 2018), MgCO 3 (Binck et al, 2020b), FeCO 3 (Cerantola et al, 2017) and…”
Section: Introductionmentioning
confidence: 99%
“…A recent remarkable discovery are carbonates, in which sp 3 -hybridization of carbon leads to the formation of CO 4 4tetrahedra instead of triangular sp 2 -hybridized CO 3 3--groups (Binck et al, 2020b;Boulard et al, 2011Boulard et al, , 2012Boulard et al, , 2015Cerantola et al, 2017;Merlini et al, 2015Merlini et al, , 2017Lobanov et al, 2017). It is now of great interest to determine whether carbonates with sp 3hybridized carbon form solid solutions with their silicate analogs and thus provide an alternative major host of carbon in the deeper mantle regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation